2009
DOI: 10.1038/ki.2009.117
|View full text |Cite
|
Sign up to set email alerts
|

The kidney is the major site of S-adenosylhomocysteine disposal in humans

Abstract: S-adenosylhomocysteine (SAH), the metabolic precursor of homocysteine in the body, is a potent inhibitor of methylation reactions. Several methylation reactions play a major role in epigenetic regulation of protein expression, atherosclerosis, and cancer development. Here we studied the mechanisms responsible for the maintenance of circulating SAH levels by measurement of the arterio-venous differences across the kidney, splanchnic organs, and the lung in humans. The lungs did not remove or add any circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…44 Furthermore, in patients with CKD, SAH accumulates more compared with homocysteine because the kidneys are the major site of SAH disposal in humans. 45 In accordance, in this study, we observed higher differences in SAH levels (30.9-fold increase in patients on dialysis) than in homocysteine levels (2.4-fold) and SAM levels (4.8-fold).…”
Section: 41supporting
confidence: 78%
“…44 Furthermore, in patients with CKD, SAH accumulates more compared with homocysteine because the kidneys are the major site of SAH disposal in humans. 45 In accordance, in this study, we observed higher differences in SAH levels (30.9-fold increase in patients on dialysis) than in homocysteine levels (2.4-fold) and SAM levels (4.8-fold).…”
Section: 41supporting
confidence: 78%
“…259 260 A significant amount of homocysteine metabolism occurs in the kidney [47] and this tissue has 261 been shown to be a major factor under other conditions, such as diabetes, that are characterized 262 by aberrant homocysteine balance [30]. Although the expression of BHMT in the rodent kidney 263 is quite low [48], we found that exercise resulted in a significant increase in renal BHMT activity 264 in the control diet group, as well as the folate-restricted group. It is not clear whether these 265 alterations in renal BHMT activity are biologically sufficient to explain the prevention of 266 hyperhomocysteinemia by exercise.…”
mentioning
confidence: 76%
“…Since most cells lack transsulfuration enzymes, excess SAH and homocysteine produced as a consequence of normal methylation processes are transported to liver and kidneys for catabolism (122). Circulating homocysteine concentrations reflect the efficacy of catabolism in the liver and kidneys (123)(124)(125).…”
Section: Hepatic and Renal Functionmentioning
confidence: 99%
“…The kidney is the major site of SAH disposal (122), and renal tubules avidly reabsorb homocysteine (134). Hence, normal kidney function comprises handling most of the homocysteine produced in the body.…”
Section: Hepatic and Renal Functionmentioning
confidence: 99%